PKCζ in prostate cancer cells represses the recruitment and M2 polarization of macrophages in the prostate cancer microenvironment - Hui-hui Fan; Ling Li; Yu-ming Zhang; Jie Yang; Mao-cheng Li; Fang-yin Zeng; Fan Deng (Tumor Biology)
Tumor-associated macrophages are key regulators of the complex interplay between tumor and tumor microenvironment. M2 Macrophages, one type of tumor-associated macrophages, are involved in prostate cancer growth and progression. Protein kinase C zeta has been shown to suppress prostate cancer cell growth, invasion, and metastasis as a tumor suppressor; however, its role in chemotaxis and activation of tumor-associated macrophages remains unclear. Here, we investigated the role of protein kinase C zeta of prostate cancer cells in regulation of macrophage chemotaxis and M2 phenotype activation. Immunohistochemistry was performed to analyze the expression of protein kinase C zeta and the number of CD206+ M2 macrophages in human prostate tissue. Macrophage chemotaxis and polarization were examined using Transwell migration assays and a co-culture system. Quantitative real-time polymerase chain reaction, western blotting, and enzyme-linked immunosorbent assay were used to detect M2 markers, protein kinase C zeta, interleukin-4, and interleukin-10 expression. We found the expression of protein kinase C zeta increased in prostate cancer tissues, especially in the early stage, and was negatively associated with tumor grade and the number of CD206+ macrophages. Inhibition of protein kinase C zeta expression in prostate cancer cells promoted chemotaxis of peripheral macrophages and acquisition of M2 phenotypic features. These results were further supported by the finding that silencing of endogenous protein kinase C zeta promoted the expression of prostate cancer cell–derived interleukin-4 and interleukin-10. These results suggest that protein kinase C zeta plays an important role in reducing infiltration of tumor-associated macrophages and activation of a pro-tumor M2 phenotype, which may constitute an important mechanism by which protein kinase C zeta represses cancer progression.